Mobile Hybrid Application Sebagai Solusi Dalam Pelaporan Bencana Menggunakan Framework Cordova - Ari Muzakir; Eksen Hidiansah (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Mobile devices are now almost used by all walks of life. Various platforms available on smartphones like Android, iOS, Windows Mobile provide great opportunities and become a challenge for app developers. The problem is that app developers need to be able to match the needs of the available platform. The solution to this problem is the mobile hybrid application technology, which enables application developers to bridge every different smartphone platform using the cordova framework. The Cordova framework allows application developers to build mobile applications using HTML5, CSS, and javascript (JS). In this research more focused on testing the technology of mobile hybrid application to build mobile application of disaster reporting at Regional Disaster Management Agency (BPBD) South Sumatera. Test results in the form of android and windows phone applications through several tests, among others, ease in the process of building applications, publishing, and configuration. It is expected that this hybrid mobile application software can help disaster management agencies in southern Sumatra region in disaster preparedness in the community.